2019
DOI: 10.9734/jgeesi/2019/v19i130077
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Poverty-Environment Relationship from Sustainable Development Perspectives

Abstract: Many observers conceptualize the environment-poverty link as “downward spiral,” with population growth and social exclusion leading to environmental deterioration. However, recent micro and small scale existential study challenges this model, showing striking heterogeneity in natural resource management by the poor, including display of their success in adapting to environmental change and the efficacy of policies in affecting outcomes. Using both conceptual and empirical material, this article aims to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…In the first instance, the poverty-environment discourse focused predominantly on "downward spirals" and one-dimensional aspects (how poverty among people causes environmental degradation) or feedback loops (how environmental degradation in return affects the poor). More recent research recognized that the poverty-environment nexus is multi-dimensional, governed by a complex web of factors, and more attention now goes to investigating how marginalized communities are able to invent and maintain protective measures that can help minimize the negative impact of environmental degradation on their ecosystems and associated livelihoods through collective action [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the first instance, the poverty-environment discourse focused predominantly on "downward spirals" and one-dimensional aspects (how poverty among people causes environmental degradation) or feedback loops (how environmental degradation in return affects the poor). More recent research recognized that the poverty-environment nexus is multi-dimensional, governed by a complex web of factors, and more attention now goes to investigating how marginalized communities are able to invent and maintain protective measures that can help minimize the negative impact of environmental degradation on their ecosystems and associated livelihoods through collective action [34].…”
Section: Discussionmentioning
confidence: 99%
“…The scientific research revealed that ensuring environmental activities and a friendly environment in society are some of the most important factors that contribute to a better supply of food to the society members, constant raise of income, as well as reducing the number of poor society members [67]. On the other hand, poor compliance of the environmental requirements, and only a few business initiatives being oriented to this field, negatively affect the increase in environmental pollution, faster consumption of resources, likewise, contributing to the increase in poverty in a country [68]. Though the last tendencies are best observed in developing countries with a low living standard, developing countries encounter the same problems, because all of them are dependent on natural resources and their exploitation [69].…”
Section: Links Between Social Responsibility and Povertymentioning
confidence: 99%
“…As causas da degradação ambiental, de acordo com Rodrigues, Cunha, Brito e Pires (2016), têm sido amplamente explanadas. Alguns autores (Masron & Subramaniam, 2019;Rai, 2019;Akinlo & Dada, 2021) correlacionam a degradação com a pobreza, enquanto outros (Isik, Ongan & Özdemir, 2019;Wang & Dong, 2019;Muhammad et.al, 2021) apontam o crescimento econômico como principal determinante. Posto isto, Sousa, Sousa e Santos (2016) afirmam que o crescimento econômico foi considerado por muito tempo como um fator negativo, tendo em vista a visão de que é o causador dos impactos ambientais, devido aos recursos para criação de mercadorias sempre serem provenientes do desgaste da natureza.…”
Section: Introductionunclassified